Prevalence of anti-hepatitis C virus antibodies in pregnant women and their offspring in a tertiary hospital in Southwestern Nigeria - Paul Sunday Ogunro,1 Daniel Adebode Adekanle,2 Francis Folorunso Fadero,3 Titus Olabisi Ogungbamigbe,4 Samuel Olorunyomi Oninla.3 (The Journal of Infection in Developing Countries, 2007)
Background: The aim of this prospective study was to determine the prevalence of HCV antibodies among pregnant women and their corresponding offspring in a tertiary medical centre in Southwestern Nigeria.Method: Anti-HCV antibodies (anti-HCV antibodies) were analyzed in blood samples from mothers and cord samples from their corresponding offspring using the Enzyme Linked Immunosorbent Assay (ELISA) method. The results obtained from the study were expressed in simple percentages.Results: Out of the 272 consenting pregnant women screened for anti-HCV antibodies, 25 (9.2%) of them were positive. As none of the pregnant women had multiple births, screening the 272 cord sera from their offspring for the same antibodies revealed that 3 (1.10%) of them were also positive. Thus, the prevalence of anti-HCV antibodies in the pregnant women and their offspring were 9.2% and 1.1% respectively.Conclusion: If vertical transmission of HCV were to be based on the acquisition of anti-HCV antibodies alone, the prevalence of vertical transmission from HCV infected mothers to offspring in the study was 12.0%. Further studies on vertical transmission are suggested to include analysis for HCV-RNA quantification in pregnant mothers and their offspring as well as a long-term follow-up of neonates seropositive for HCV markers. Such studies are necessary to justify any recommendations to be made for the purpose of reducing HCV infection through vertical transmission.